SABERES DE ENCATERIAS E A FITOTIPIA: : UM FAZER INTERDISCIPLINAR E SUAS INFLEXÕES EPISTEMOLÓGICAS NA FORMAÇÃO INICIAL DOCENTE AMAZÔNIDA (Revista NUPEART, 2026)
This study investigates phytotype as a practice of memory and ancestry in initial visual arts training in the Amapá Amazon. The series "Rastro Ancestral" by Elenir Santos uses family albums and sunlight to reveal images on leaves — a process that refuses digital haste. The work was developed at the xxxx Laboratory at xxxxx and connects knowledge from encanterias and embodied knowledge to arts education, questioning Eurocentric logic and academic fragmentation. Research and creation walk together, transforming teaching praxis. The exhibition "Imagens Insurgentes" concretizes this path: manual touch and respect for nature's cycles promote a sensitive and decolonial education. Phytotype ceases to be merely technique and becomes a political gesture — honoring the past and drawing other ways of teaching and existing in the Amazonian territory.